The effect of adverse intrauterine conditions, early childhood growth and famine exposure on age at menopause: a systematic review. (4th December 2017) - Sadrzadeh, S.; Verschuuren, M.; Schoonmade, L. J.; Lambalk, C. B.; Painter, R. C.
Abstract : When the follicle reserve, which is developed solely during the fetal period, is depleted, women enter menopause. Intrauterine and childhood adverse conditions might affect the ovarian capacity by influencing follicle production in the first trimester, limiting the initial follicle pool or mediate an accelerated follicular loss thereafter. To investigate if adverse early life influences result in younger age at menopause, the following online databases were systematically searched: PubMed, EMBASE, CINHAL (EBSCO) and Cochrane library (Wiley) up to 1 January 2017. Eligibility, data extraction and quality assessment was independently performed by two researchers. A total of 5278 studies were identified, 11 studies were deemed eligible and included. Nine were cohort studies, 1 case–control study and 1 twin study. Due to the diversity of reported data and risk estimates we were unable to pool data or perform meta-analysis on pooled data. Prenatal and childhood exposure to famine was significantly associated to an earlier age at menopause in three studies. Mean differences in age at menopause varied from 4 months up to 1.7 years between famine exposed and unexposed women. Three studies described a significant association between a low weight at ages 1 or 2 and a younger age at menopause. A younger age at menopause was associated with a higher weight at birth in only one study and with a high ponderal index, a measure for fatness at birth in another study. None of the nine studies reporting on low birth weight and age at natural menopause find a significant association.